2016
DOI: 10.25100/cm.v47i1.1975
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study of leptospirosis and fetal death in Yucatan, Mexico

Abstract: Introduction: Leptospirosis is a zoonotic disease affecting mainly to low income human population. Acute leptospiral infection during pregnancy has been associated with spontaneous abortion and fetal death during the first trimester and the abortion may occur as consequence of systemic failure. Objective: To estimate the frequency of Leptospira interrogans infection in women with spontaneous abortion in the state of Yucatan, Mexico. Methods: A cross sectional study on women with spontaneous abortion was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
10
0
2
Order By: Relevance
“…For the case reports, the majority of cases were in urban areas (70%, n = 23). One cross sectional study (Study 4, Table 1) based in Yucatan, Mexico found a higher frequency of leptospirosis in pregnancy leading to spontaneous miscarriage in rural areas (4%) compared to urban (1.3%) [17].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the case reports, the majority of cases were in urban areas (70%, n = 23). One cross sectional study (Study 4, Table 1) based in Yucatan, Mexico found a higher frequency of leptospirosis in pregnancy leading to spontaneous miscarriage in rural areas (4%) compared to urban (1.3%) [17].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…This was due to a general paucity of data on leptospirosis in pregnancy, combined with the heterogeneity of the study population which provided the denominator for the rates. Two studies looked at seroprevalence of leptospirosis in febrile pregnant women [18,20], two studies at seroprevalence of leptospirosis in jaundiced pregnant women [19,22], one explored cases of leptospirosis in women who had spontaneous abortion [17], another on leptospirosis as a cause of abortion, stillbirth or developmental anomalies [24]. One cross-sectional study looked at seroprevalence of leptospirosis in 442 healthy pregnant women across 10 Caribbean countries [17,20,21], and one investigating causes of fever and pulmonary syndrome in pregnant women, where no cases of leptospirosis were identified [22,23].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…IgM ELISA, IgM/immunoglobulin G (IgG) ELISA, and real-time DNA polymerase chain reaction of blood, urine & CSF are some of the laboratory procedures used to detect for leptospirosis (CSF). A single titre of 1:200 IgM antibodies or a four-fold increase in microscopic agglutination testing titre collected during the 1st and 4th week of sickness, or body fluids or tissue cultures of leptospires are used to make a diagnosis of leptospirosis [4]. These patients have responded well to medicines such as penicillin G, streptomycin, chloramphenicol, doxycycline and erythromycin [4].…”
Section: Discussionmentioning
confidence: 99%
“…A single titre of 1:200 IgM antibodies or a four-fold increase in microscopic agglutination testing titre collected during the 1st and 4th week of sickness, or body fluids or tissue cultures of leptospires are used to make a diagnosis of leptospirosis [4]. These patients have responded well to medicines such as penicillin G, streptomycin, chloramphenicol, doxycycline and erythromycin [4]. According to the WHO, depending on the stage of pregnancy, leptospirosis can cause abortion, foetal death, stillbirth, or congenital leptospirosis in women [5].…”
Section: Discussionmentioning
confidence: 99%